Penerapan Konsep Finite State Automata (FSA) pada Mesin Pembuat Ice Cream Otomatis - Fergie Joanda Kaunang (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2019)
Technology is a tool that helps humans in carrying out an activity. With the use of technology in the industrial field, more goods are being produced. One type of technology that has a large part in the industry is automatic machinery. An automatic machine is a series of technologies intended to change activities that are manual to automatic that have the aim to improve the process of making goods, and have a higher quality product. Automata Theory is a branch of science that is not yet well known to many people but has an important role in the field of computer science. The main concept of the automata theory itself is how to make machines work automatically. Therefore, this study aims to apply the concept of the Automata theory to the automatic ice cream maker. This study discusses two methods for analyzing and supporting applications which are simulations of the ice cream maker itself. The formal method used to analyze the workings from reading the input to updating to give the final result of the machine. Another method used is the prototyping method where this method is used for the application of automatic ice cream maker applications in this study. The results of this study indicate that Finite State Automata can be an alternative for analyzing automatic ice cream making machines by reading the input provided by the user and then developing the patterns used.